Conserving African Ungulates Under Climate Change: Do Communal and Private Conservancies Fill Gaps in the Protected Area Network Effectively? - Payne, Benjamin Luke; Bro-Jørgensen, Jakob (Frontiers in Ecology and Evolution, 2020)
Throughout Africa, conservancies under community and private management are becoming increasingly important as a complement to the protection offered by the established core network of protected areas, which are largely under national management. However, opportunities for creating new conservation areas are restricted by increasing demand on land use by growing human populations, and it is unclear how effectively the current protected area network captures spatial priorities for conservation. Taking into account climate-induced range-shifts, we first identified spatial priorities for antelope conservation in Africa by gap analysis of the network of protected areas listed with an IUCN category in the World Database for Protected Areas. For three countries from which information were available, we then assessed to what extent the gaps identified were covered by protected areas not listed with an IUCN category, for the latter making a distinction between whether management was referred to as community-based or not. The results showed limited overlap, indicating that the success of community-based and privately managed protected areas in covering spatial priorities from a continent-wide perspective could be increased by more strategic land use planning at the national level.